Applications of Nanotechnology in Animal Reproduction: An Overview - Rasool, Akhter; Sakthivel, Jeyakumar; Gowdar Veerappa, Vedamurthy; Mahendra Abhonkar, Rohit; Misal, Snehal (The Indian Journal of Animal Reproduction, 2025)
Nanotechnology is revolutionizing reproductive management in farm animals. This cutting-edge field enables preci sion interventions in assisted reproductive techniques (ART), including advanced drug delivery systems, cryopreser vation technologies, and manipulation of gametes and embryos. Nanoparticle-based extenders, such as selenium (Se)  and nano-zinc oxide (ZnO), mitigate oxidative stress during cryopreservation, improving sperm viability and post-thaw  motility. Controlled-release systems utilizing polymeric and metal-based nanoparticles facilitate the sustained deliv ery of reproductive hormones like progesterone and GnRH, optimizing estrous synchronization and superovulation.  Additionally, herbal-extracted nanoparticles, such as those from Moringa oleifera and Curcuma caesia, exhibit potent  antioxidant properties, further enhancing sperm preservation. Quantum dots provide real-time insights into fertilization  dynamics, while biosensors, including L-tyrosine silver nanoparticles, improve estrus detection rate. Despite these prom ising advancements, challenges such as regulatory hurdles, high production costs, and concerns regarding nanoparticle  toxicity persist. Future research aims to refine these technologies for enhanced safety, cost-effectiveness, and seamless  integration into sustainable livestock breeding programs.
Keywords: Animal reproduction; Drug delivery; Diagnostic; Nanotechnology; Nanocarrier